2019
DOI: 10.1093/carcin/bgz130
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma cell-derived exosomes affect tumor microenvironment by specific packaging of microRNAs

Abstract: Abstract Bone microenvironment provides growth and survival signals essential for osteosarcoma (OS) initiation and progression. OS cells regulate communications inside tumor microenvironment through different ways and, among all, tumor-derived exosomes support cancer progression and metastasis. To define the contribution of OS-derived exosomes inside the microenvironment, we investigated the effects induced in bone remodeling mechanism and tumor angiogenesis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 70 publications
2
110
0
Order By: Relevance
“…Interestingly, exosomes can carry numerous miR-NAs that act locally or enter into circulation to act at distal sites, since internal miRNAs are protected from being digested by RNase, as a result of the protection offered by the lipid membrane of the exosomes [12,13]. New evidence has demonstrated that exosomal miRNAs (exo-miRNAs) transmitted between cells perform a crucial regulatory function in apoptosis, invasion, migration, proliferation, as well as chemoresistance of multifarious tumors, including GC [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, exosomes can carry numerous miR-NAs that act locally or enter into circulation to act at distal sites, since internal miRNAs are protected from being digested by RNase, as a result of the protection offered by the lipid membrane of the exosomes [12,13]. New evidence has demonstrated that exosomal miRNAs (exo-miRNAs) transmitted between cells perform a crucial regulatory function in apoptosis, invasion, migration, proliferation, as well as chemoresistance of multifarious tumors, including GC [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, studies found that exosomes were significantly different in composition in various diseases, which was mainly owing to changes in the cytoplasmic physiology 9,10 . For instance, osteosarcoma cell‐derived exosomes affected the tumor microenvironment by specific packaging of microRNA 11 . These differentially expressed bioinformatic molecules in exosomes are one of the important factors affecting the development of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Validation studies using metastatic and non-metastatic exosome transfer and mimic treatments confirmed that the uptake of miR-675 via exosomes led to the downregulation of CALN1 expression associated with migration [100]. A more recent study has investigated if OS-derived exosomes could induce changes to macrophages, osteoclasts, and endothelial cells, important components of the TME [101]. Exosome internalization by macrophages induced osteoclast gene expression profile and an increase in the number of osteoclast-like cells.…”
Section: Exosomes In Osmentioning
confidence: 93%
“…Exosome internalization by macrophages induced osteoclast gene expression profile and an increase in the number of osteoclast-like cells. In addition, osteoclasts cultured with OS-derived exosomes had higher bone resorption activity in vitro [101], suggesting that OS could induce changes in the bone microenvironment via macrophage and osteoclast modulation. Moreover, the uptake of OS-derived exosomes by endothelial cells induced an increase in pro-angiogenic factors and the formation of capillary structures in vitro, thus confirming that OS could modulate the invasiveness of cancer cells by modulating the TME [101].…”
Section: Exosomes In Osmentioning
confidence: 99%
See 1 more Smart Citation